Gelatin Microspheres as Vehicle for Cardiac Progenitor Cells Delivery to the Myocardium. Issue 9 (23rd February 2016) - Feyen, Dries A. M.; Gaetani, Roberto; Deddens, Janine; van Keulen, Danielle; van Opbergen, Chantal; Poldervaart, Michelle; Alblas, Jacqueline; Chamuleau, Steven; van Laake, Linda W.; Doevendans, Pieter A.; Sluijter, Joost P. G.
Abstract : Inadequate cell retention and survival in cardiac stem cell therapy seems to be reducing the therapeutic effect of the injected stem cells. In order to ameliorate their regenerative effects, various biomaterials are being investigated for their potential supportive properties. Here, gelatin microspheres (MS) are utilized as microcarriers to improve the delivery and therapeutic efficacy of cardiac progenitor cells (CPCs) in the ischemic myocardium. The gelatin MS, generated from a water‐in‐oil emulsion, are able to accommodate the attachment of CPCs, thereby maintaining their cardiogenic potential. In a mouse model of myocardial infarction, we demonstrated the ability of these microcarriers to substantially enhance cell engraftment in the myocardium as indicated by bioluminescent imaging and histological analysis. However, despite an observed tenfold increase in CPC numbers in the myocardium, echocardiography, and histology reveals that mice treated with MS‐CPCs show marginal improvement in cardiac function compared to CPCs only. Overall, a straightforward and translational approach is developed to increase the retention of stem cells in the ischemic myocardium. Even though the current biomaterial setup with CPCs as cell source does not translate into improved therapeutic action, coupling this developed technology with stem cell‐derived cardiomyocytes can lead to an effective remuscularization therapy. Abstract : Gelatin microspheres are perfectly fitted for the delivery of stem cells to the heart. The biocompatibility of these microcarriers allows for cardiac progenitor cells attachment to their surface. Once the cellular cargo is loaded, microcarriers can effectively improve the retention and survival of the attached cells. Additionally, their size allows for administration through a clinically relevant noninvasive cardiac injection‐catheter.